Dietary Effects of Different Proportions of Fermented Straw as a Corn Replacement on the Growth Performance and Intestinal Health of Finishing Pigs - Xiaoguang Ji; Wenfei Tong; Xiangxue Sun; Lei Xiao; Mengjun Wu; Peng Li; Yonggang Hu; Yunxiang Liang (Animals)
The aim of the present study was to investigate the dietary effects of replacing corn with different proportions of fermented straw on the growth performance and intestinal health of finishing pigs. A total of 275 healthy commercial finishing pigs aged 126 days (average body weight, 82.96 ± 3.07 kg) were randomly allocated into three groups: the control (CTR, basal diet) group, the 5% fermented straw (FJJG5, replacing 5% of the corn) group, and the 10% fermented straw (FJJG10, replacing 10% of the corn) group. There were six replicates in each group and 14–16 pigs per replicate. On day 39 of the experiment, one animal from each replicate was slaughtered for sampling and for further analysis. The results showed that the finishing pigs in the FJJG10 group had a reduced average daily weight gain and an increased feed-to-gain ratio. The FJJG5 group had reduced total cholesterol, high-density lipoprotein, and low-density lipoprotein in their serum, while the FJJG5 and FJJG10 groups had reduced contents of lactate dehydrogenase. In addition, the FJJG5 group exhibited increased T-SOD activity and MDA content in the colon, while the FJJG10 group also showed increased T-AOC activity in their serum and increased contents of MDA in the colon. The FJJG5 group exhibited increased activities of jejunal disaccharidase and lipase, while the FJJG10 group exhibited decreased jejunal crypt depths. Moreover, the FJJG5 group presented an increased relative expression of APOA4, LPL, and MUC2 but decreased SLC7A7 and IL-10 in the jejunum and APOA4 in the colon. The FJJG10 group exhibited a decreased relative expression of SLC7A7 and IL-10 in the jejunum and decreased MMP13, KCNJ13, APOA4, SLC7A7, LPL, and IL-10 in the colon. Furthermore, the FJJG5 group exhibited an increased relative abundance of Lactobacillus in colon contents, while the FJJG10 group had a reduced relative abundance of streptococcus. In conclusion, 5% fermented straw can improve the lipid metabolism and colon microbiota structure of finishing pigs, while 10% fermented straw has adverse effects on the growth performance and intestinal health of finishing pigs.